Dazzling Photoshop : how to create masterpieces in Photoshop. - Zuckerman, Jim (Master photo workshops., 2009)
"Photoshop provides the photographer with the tools to create images that sometimes only exist in our imagination. With this Photoshop video, Jim Zuckerman shows all the techniques he uses to create some of his favorite Photoshop images and will have you creating your own dazzling Photoshop masterpieces. Even though Jim starts at the beginning, this Photoshop video is not just for beginners. Because Photoshop can't be taught in a linear fashion, like mathematics, Jim quickly gets into very creative techniques that intermediate and advanced Photoshop users will love to learn. In this video, Jim uses CS4 however, this program is designed to help users of any version of Photoshop because it focuses on techniques rather than teaching a specific version of Photoshop."--Resource description page.